2006
DOI: 10.1007/s00213-006-0380-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute ethanol or amphetamine administration on the acoustic startle response and prepulse inhibition in adolescent and adult rats

Abstract: These data provide further evidence of the relative insensitivity of adolescent animals to amphetamine, although no age effects were found in terms of ethanol sensitivity using these measures of startle and sensorimotor gating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 58 publications
4
21
1
Order By: Relevance
“…For example, younger animals have been shown to develop less sensitization than adult animals following repeated exposure to stimulants such as cocaine [14], [29], amphetamine [28], and methylphenidate [9,10]. Similar results have been observed for alcohol [12], [39]. While the effects of toluene have been investigated in younger animals, the majority of these studies have focused on gestational exposure followed by later assessment of toluene's effects in pre-weanling and older animals [see review [6]].…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…For example, younger animals have been shown to develop less sensitization than adult animals following repeated exposure to stimulants such as cocaine [14], [29], amphetamine [28], and methylphenidate [9,10]. Similar results have been observed for alcohol [12], [39]. While the effects of toluene have been investigated in younger animals, the majority of these studies have focused on gestational exposure followed by later assessment of toluene's effects in pre-weanling and older animals [see review [6]].…”
Section: Introductionmentioning
confidence: 58%
“…Similar to ethanol, toluene interacts with GABA A receptors [1,2], suggesting that this mechanism may also contribute to the age differences observed in the present study. In addition, younger animals have been shown to develop less locomotor sensitization than adult animals following repeated exposure to other drugs of abuse such as alcohol [12], [39], cocaine [14], [29], amphetamine [28], and methylphenidate [9,10]. Together, these results suggest that initial sensitivity to the acute locomotor effects of toluene (and perhaps those of other inhalants) follows a developmental time-course in which sensitivity increases as rats leave adolescence and enter adulthood.…”
Section: Discussionmentioning
confidence: 93%
“…This negative finding is of special interest because the dopaminergic system has been implicated in the mode of action of modafinil and the dopaminergic system is known to play a key role in mediating PPI (Swerdlow et al, 1992;Koch and Schnitzler, 1997;Koch, 1999;Zhang et al, 2000). Indeed, it has been shown that amphetamine, a wakefulness-promoting drug acting via dopaminergic mechanisms (Bunney et al, 1973a, b;Calcagnetti and Schechter, 1992;Nishino et al, 1998;Paladini et al, 2001), disrupts PPI of the startle response in both rat (Mansbach et al, 1988;Swerdlow et al, 1990;Sills, 1999;Zhang et al, 2000;Swerdlow et al, 2003;Brunell and Spear, 2006) and human (Kumari et al, 1998;Hutchison and Swift, 1999;Swerdlow et al, 2003) startle paradigms. Although both modafinil and amphetamine promote wakefulness, modafinil does not seem to share the psychostimulant and addictive potentials of amphetamine (Simon et al, 1995;Ferraro et al, 1997;Engber et al, 1998a, b;Jasinski, 2000;Deroche-Gamonet et al, 2002;Chapotot et al, 2003), which are known to be mediated via the mesoaccumbal dopaminergic system (Di Ciano et al, 1995;Zhang et al, 2000;Di Chiara et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies from Brunell and Spear (2006) indicate that adolescents exhibit bimodal behavioral responses to alcohol, with both hypo-and hyperresponsive systems (Doremus et al, 2003;Long et al, 1992;Varlinskaya and Spear, 2002). These findings have important implications for the risks associated with recreational drinking in adolescents and young adults.…”
Section: Alcoholmentioning
confidence: 99%